GAMBARAN PROGRAM PROMOSI JABATAN, PENGHARGAAN DAN KEPUASAN KERJA KARYAWAN PT. GUNANUSA UTAMA FABRICATORS SERANG - Sari, Dwi Ervita; Senen, Syamsul Hadi; Razati, Girang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of promotion program, reward and job satsfaction. Design/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 90 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results obtained result that promotion of good enough position with score 7396 acquisition equal to 73,37%, amount in category enough according to score 12118, obtained percentage equal to 73,98%. and job satisfaction in high enough category with score 12769 Earnings equal to 75,06%.Originality/value - This study provides a basis for understanding issues of promotion program, reward and job satsfaction. The difference of this study with the previous research is located on the object which is the company in the contuction industry that is PT. Gunanusa Utama Fabricators Serang, with the variables studied namely promotion program, reward and job satsfaction, and using different theory or reference from previous researcher.